1997
DOI: 10.1046/j.1464-410x.1997.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

The biodegradable self‐reinforced poly‐dl‐lactic acid spiral stent compared with a suprapubic catheter in the treatment of post‐operative urinary retention after visual laser ablation of the prostate

Abstract: Objective To evaluate the eÃcacy and safety of a biodegdegradation time of the SR-PLA stent was 6 months; spiral fragments were found in the prostatic urethra radable self-reinforced poly-dl-lactic acid (SR-PLA) spiral stent compared with a suprapubic catheter after or the urinary bladder in 20 of the patients on cystoscopy. Improvements in patient-weighted sympvisual laser ablation of the prostate (VLAP) in a randomized study.tom score, mean Q max and PVR were significant in both groups at the 6 month follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 6 publications
1
17
0
2
Order By: Relevance
“…Stent infection rates, migration rates, and degradation rates were similar to those in other studies [20,31,32]. It was observed that the rate of prostate stent infection was related to the length of time that the suprapubic tube was left in place [33]. Stents that migrate early resulted in obstruction; those that migrated late were asymptomatic.…”
Section: Interstitial Laser Coagulationsupporting
confidence: 81%
“…Stent infection rates, migration rates, and degradation rates were similar to those in other studies [20,31,32]. It was observed that the rate of prostate stent infection was related to the length of time that the suprapubic tube was left in place [33]. Stents that migrate early resulted in obstruction; those that migrated late were asymptomatic.…”
Section: Interstitial Laser Coagulationsupporting
confidence: 81%
“…Hospitalization would be avoided and the need for prostatectomy almost certainly reduced. A biodegradable self-reinforced poly DL-lactic acid spiral stent has been described to be safe and effective for the treatment of postoperative urinary retention after visual laser ablation of the prostate (VLAP) in a randomized study [73]. Further studies are required to optimize the design, tailor the degradation sequences, incorporate properties such as radio-opacity and produce a range of biodegradable devices that degrade at different rates for different circumstances.…”
Section: Prostatic Devices/stentsmentioning
confidence: 99%
“…Zur Anwendung kam das biologisch abbaubare synthetische Homopolymer Poly-L-lactid (PLLA, Resomer ® L24 M w =650.000 g/mol, M w /M n =, 8 …”
Section: Polymer Und Pharmakonunclassified
“…Allerdings ergaben sich Komplikationen, die auf eine zu schnelle Degradation zurückgeführt wurden [8].…”
Section: Gewebekultivierungunclassified